2017
DOI: 10.4049/jimmunol.1601557
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1 Tax-Specific CTL Epitope–Pulsed Dendritic Cell Therapy Reduces Proviral Load in Infected Rats with Immune Tolerance against Tax

Abstract: Adult T cell leukemia/lymphoma (ATL), a CD4 T cell malignancy with a poor prognosis, is caused by human T cell leukemia virus type 1 (HTLV-1) infection. High proviral load (PVL) is a risk factor for the progression to ATL. We previously reported that some asymptomatic carriers had severely reduced functions of CTLs against HTLV-1 Tax, the major target Ag. Furthermore, the CTL responses tended to be inversely correlated with PVL, suggesting that weak HTLV-1-specific CTL responses may be involved in the elevatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…In a rat model of oral HTLV‐1 infection, HTLV‐1‐specific T‐cell tolerance was established with higher PVL than in rats infected through other routes, resembling the situation in HTLV‐1 carriers with impaired CTL responses. This was resolved by Tax‐DC vaccination, resulting in activation of Tax‐specific CTL responses and reduced HTLV‐1 PVL (Figure ) . This observation supports the idea of prophylactic use of Tax‐targeted vaccines in HTLV‐1 carriers with impaired Tax‐specific CTL responses.…”
Section: Tax‐targeted Vaccine As a Potential Early And/or Prophylactisupporting
confidence: 71%
“…In a rat model of oral HTLV‐1 infection, HTLV‐1‐specific T‐cell tolerance was established with higher PVL than in rats infected through other routes, resembling the situation in HTLV‐1 carriers with impaired CTL responses. This was resolved by Tax‐DC vaccination, resulting in activation of Tax‐specific CTL responses and reduced HTLV‐1 PVL (Figure ) . This observation supports the idea of prophylactic use of Tax‐targeted vaccines in HTLV‐1 carriers with impaired Tax‐specific CTL responses.…”
Section: Tax‐targeted Vaccine As a Potential Early And/or Prophylactisupporting
confidence: 71%
“…Promising new therapies include vorinostat and romidepsin (histone deacetylase inhibitors), alemtazumab (anti-CD52 antibody), and brentuximab vedotin (anti-CD30 antibody) [ 468 ]. A recent animal model indicated that pulsed dendritic cell therapy may decrease PVL by stimulating HTLV-1 responsive cytotoxic lymphocytes [ 469 ]. A pilot clinical trial using belinostat in combination with AZT-based maintenance therapy for aggressive leukemic ATL types is currently underway (NCT02737046).…”
Section: Human T-cell Lymphotropic Virus-1mentioning
confidence: 99%
“…These ACs may be the possible target population for prophylactic therapy. In a rat model of oral HTLV-1 infection with immune tolerance, Tax-DC vaccine successfully induced Tax-specific CTLs and reduced the HTLV-1 proviral load, suggesting the promising prophylactic potential of Tax-targeting vaccines against ATL [127].…”
Section: Significance Of Tax-targeted Therapeutic Vaccine In the Antimentioning
confidence: 99%